Preoperative Warming Versus no Preoperative Warming for Maintenance of Normothermia in Women Receiving Intrathecal Morphine for Cesarean Delivery: A Single-Blinded, Randomized Controlled Trial. (January 2018) - Munday, Judy; Osborne, Sonya; Yates, Patsy; Sturgess, David; Jones, Lee; Gosden, Edward
Abstract : BACKGROUND: Rates of hypothermia for women undergoing spinal anesthesia for cesarean delivery are high and prevention is desirable. This trial compared the effectiveness of preoperative warming versus usual care among women receiving intrathecal morphine, which is thought to exacerbate perioperative heat loss. METHODS: A prospective, single-blinded, randomized controlled trial compared 20 minutes of forced air warming (plus intravenous fluid warming) versus no active preoperative warming (plus intravenous fluid warming) in 50 healthy American Society of Anesthesiologists graded II women receiving intrathecal morphine as part of spinal anesthesia for elective cesarean delivery. The primary outcome of maternal temperature change was assessed via aural canal and bladder temperature measurements at regular intervals. Secondary outcomes included maternal thermal comfort, shivering, mean arterial pressure, agreement between aural temperature, and neonatal outcomes (axillary temperature at birth, Apgar scores, breastfeeding, and skin-to-skin contact). The intention-to-treat population was analyzed with descriptive statistics, general linear model analysis, linear mixed-model analysis, χ 2 test of independence, Mann-Whitney, and Bland-Altman analysis. Full ethical approval was obtained, and the study was registered on the Australia and New Zealand Clinical Trials Registry (Trial No: 367160, registered athttp://www.ANZCTR.org.au/ ). RESULTS: Intention-to-treat analysis (n = 50) revealed no significant difference in aural temperature change from baseline to the end of the procedure between groups: F (1, 47) = 1.2, P = .28. There were no other statistically significant differences between groups in any of the secondary outcomes. CONCLUSIONS: A short period of preoperative warming is not effective in preventing intraoperative temperature decline for women receiving intrathecal morphine. A combination of preoperative and intraoperative warming modalities may be required for this population. Abstract : Published ahead of print May 12, 2017.